Assessing the application of barbed sutures in comparison to conventional sutures for surgical applications: a global systematic review and meta-analysis of preclinical animal studies - Xiang, Nanyan; Lin, Yifei; Su, Xiaoyi; Hu, Zifan; Zhou, Jinyu; Wu, Yi; Du, Liang; Huang, Jin (International journal of surgery (London, England), 2024)
Following an initiative published by Lancet in 2002 and an IDEAL-D framework, the value of preclinical animal studies has garnered increasing attention in recent research. Numerous preclinical animal experiments tried to generate evidence to guide the development of barbed sutures. However, discernible drawbacks and incongruities in outcomes have emerged between clinical and preclinical animal studies. Therefore, this meta-analysis aimed to review the preclinical animal experiments comparing barbed sutures with conventional sutures. The authors hope to facilitate clinical translation of barbed sutures by evaluating effectiveness, safety, and physical properties/reliability. A systematic search of PubMed, EMBASE, Cochrane Library, and ClinicalTrials.gov was conducted to identify controlled preclinical animal experiments comparing barbed sutures with conventional sutures. The risk of bias was assessed using SYRCLE. GRADE approach was used to evaluate evidence quality. Revman was applied to analyze all the data. Subgroup, sensitivity, and meta-regression analyses were also performed. A total of 62 articles were eligible with low to moderate quality, including 2158 samples from 10 different animal species across 27 surgical procedures. Barbed suture exhibited a significant reduction in suture time, limited change in Cross-Sectional Area (CSA), and decreased instances of tissue disruption (all P <0.05). Subgroup analyses, considering both clinical and research significance, indicated that barbed sutures might cause more specific adverse events and demonstrate suboptimal performance of physical properties/reliability. Meta-regression suggested that heterogeneity resulted from variations in studies and animal models. Although barbed suture demonstrated superiority in numerous surgeries for time efficiency, its safety and physical properties/reliability might be influenced by diverse preclinical models, sutures' brand, surgeries, and anatomical sites. Further evaluation, based on standardized and well-designed animal experiments, is essential for medical device development and applications in human beings.